Harmonic Fractals in the Brain: Transient Tuning and Synchronic Coordination in the Quasi-Chaotic Background of Ongoing Neural Eeg Activity - Cordova-Gonzalez, F; Diaz-Munoz, H (Elsevier B.V., 2013)
Despite the long-time that EEG has been used in neurophysiological characterization of the brain functioning and the diverse methods that has been used to enhance its predictive power, frequency resolution and time dependent description of EEG features, it remain at the level of gross depictions. By mean of collapsing time, through doing a power spectrum analysis, the focus is put on amplitude differences among wide EEG (delta, theta, alpha, beta and gamma) frequency bands or, without any further consideration of the mid- or long-term time course evolution, of the ever changing neural processes of the brain. To try to solve this, we took an exploratory approach that consider both weaknesses of the problem by taking into account, simultaneously, the synchrony of the time course of the EEG signal and the harmonic tuning among single narrow short-time frequency bands along the whole spectrum from 0, 5 to 60 Hz. To characterize the neural phenomena in these terms we cleaned and selectively filtered and transformed the EEG signal into music, and used the so-transformed EEG recording to find harmonic fractal elements in it during the execution of a number of exploratory basal and experimental tests in humans. We sustained our search on the fact that EEG signal can be described as a particular type of quasi-predictable noise, also called pink or fractal noise. We looked for detection of specific and transient synchronized and wide tuned elements of EEG brain activity characterized by high self-similarity or high values of statistical autocorrelation expressed in regular shaped associated plots. We found and characterized harmonic fractals coming from EEG of 5 subjects during the execution of three exploratory experimental conditions: basal resting state with eyes open and closed; a cognitive challenge consisting in the execution of an abbreviated version of the Raven visual intelligence test; and during four minutes playing an action video game. Results showed the presence of characteristic harmonic fractals in all the conditions tested and revealed intra and inter-individual differences that can eventually be used to characterize particular brain activity states related to specific sensory, or cognitive, processes or may be indicating individual differences in the way to process information, in particular situations, developmental stage, illness or neuropsychological disorders. © 2013 The Authors. Published by Elsevier B.V.